Evolution of moth sex pheromone composition by a single amino acid substitution in a fatty acid desaturase - Buček, Aleš; Matoušková, Petra; Vogel, Heiko; Šebesta, Petr; Jahn, Ullrich; Weißflog, Jerrit; Svatoš, Aleš; Pichová, Iva (Proceedings of the National Academy of Sciences of the United States of America, 2015)
For sexual communication, moths primarily use blends of fatty acid derivatives containing one or more double bonds in various positions and configurations, called sex pheromones (SPs). To study the molecular basis of novel SP component (SPC) acquisition, we used the tobacco hornworm (Manduca sexta), which uses a blend of mono-, di-, and uncommon triunsaturated fatty acid (3UFA) derivatives as SP. We identified pheromone-biosynthetic fatty acid desaturases (FADs) MsexD3, MsexD5, and MsexD6 abundantly expressed in the M. sexta female pheromone gland. Their functional characterization and in vivo application of FAD substrates indicated that MsexD3 and MsexD5 biosynthesize 3UFAs via E/Z14 desaturation from diunsaturated fatty acids produced by previously characterized Z11-desaturase/conjugase MsexD2. Site-directed mutagenesis of sequentially highly similar MsexD3 and MsexD2 demonstrated that swapping of a single amino acid in the fatty acyl substrate binding tunnel introduces E/Z14-desaturase specificity to mutated MsexD2. Reconstruction of FAD gene phylogeny indicates that MsexD3 was recruited for biosynthesis of 3UFA SPCs in M. sexta lineage via gene duplication and neofunctionalization, whereas MsexD5 representing an alternative 3UFA-producing FAD has been acquired via activation of a presumably inactive ancestral MsexD5. Our results demonstrate that a change as small as a single amino acid substitution in a FAD enzyme might result in the acquisition of new SP compounds.
Keywords: molekulární evoluce; sexuální lákadla; Amino Acid Substitution; Fatty Acids, Unsaturated; Phylogeny; nenasycené mastné kyseliny; Molecular Sequence Data; Evolution, Molecular; molekulární sekvence - údaje; Manduca sexta; hmyzí proteiny; Female; Sex Attractants; sex pheromone biosynthesis; zvířata; substrate specificity; pheromone evolution; Amino Acid Sequence; desaturasy mastných kyselin; ženské pohlaví; Manduca; substituce aminokyselin; Fatty Acid Desaturases; fylogeneze; fatty acid desaturase; Animals; Insect Proteins; sekvence aminokyselin